A Comparison of the Concept of Justice in Natural Law and Positive Law: Its Relevance to Law Enforcement Practices in Indonesia - Hia, Imelda Indah Putri; Triadi, Irwan (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This research is motivated by the tension between formal legal certainty and demands for substantive justice in law enforcement practices in Indonesia. This study aims to analyze and compare the concepts of justice from the perspectives of natural law and positive law, and to assess their relevance in the national legal system. The research method used is normative juridical with a descriptive-analytical approach through a literature review of primary, secondary, and tertiary legal materials. The results show that natural law emphasizes justice based on universal moral principles (substantial justice), while positive law focuses on compliance with formal procedures and norms (procedural justice). The Indonesian legal system, based on Pancasila, conceptually seeks to synthesize these two perspectives, as reflected in the obligation of judges to explore the values of social justice. However, the dominance of legal positivism still creates a gap between legal certainty and a sense of social justice. The implications of this research emphasize the need for a balance between legal certainty and moral justice to make Indonesian law more meaningful and substantively just.